Pythagoras Theorem- Introduction and Examples

The Pythagorean Theorem 

If a and b are the lengths of the legs of a right triangle and c is the length of the hypotenuse, then the sum of the squares of the lengths of the legs is equal to the square of the length of the hypotenuse. This relationship is represented by the formula: +=


Let assume the length of sides of ▲abc,
    = 2, b = 3 and, c = ?
  Now, Find the length of C-
So, according to Pythagoras theorem, a² + b²= c²
now, 2² + 3² = c² = 13
now, c² = 13,
 c = √13

Post a comment